Wise Outlet / Nur Afiqah Mohamad Sufi - Mohamad Sufi, Nur Afiqah (2020)
Smartlet Sdn Bhd is proudly presents the smartest outlet in the current market that can do better than the regular outlet at home. We named after it the Wise Outlet because this outlet is smart enough to remind users when their electronic devices are completely charge. It will produce sound when the discs inside the buzzer expand and vibrate due to the undesired electric current pass through it. The small signal produce from the vibration will be transmitted to the audio amplifier to make it bigger enough to be transferred to the speaker. To narrow down our company target market, we mainly focus on marketing our product for working and studying adults. This is because, they tend to have more buying power considering their age and stable source of income. Secondary target market also has been identified by our company by using the market segmentations such as geographic, demographic and psychographic as these also can contribute to our profits. In the early production years, we will be focusing on marketing our product to every state in Malaysia. Once our brand become stable and well-known enough among the locals, we might expand our product to the neighbouring country such as Indonesia, Thailand, Singapura and eventually venture into the worldwide market.